Validity of a virtual reality endoscopic retrograde cholangiopancreatography simulator: can it distinguish experts from novices? - Georgiou, Konstantinos; Boyanov, Nikola; Antonakis, Pantelis; Thanasas, Dimitrios; Sandblom, Gabriel; Enochsson, Lars (Frontiers in Surgery, 2023)
Background There is a lack of evidence regarding the effectiveness of virtual simulators as a means to acquire hands-on exposure to endoscopic retrograde cholangiopancreatography (ERCP). The present study aimed to assess the outcome and construct validity of virtual ERCP when training on the GI II Mentor simulator. Methods A group of seven experienced endoscopists were compared with 31 novices. After a short introduction, they were requested to carry out three virtual ERCP procedures: diagnosing and removing a common bile duct (CBD) stone; diagnosing and taking brush cytology from a hilar stenosis; and, finally, diagnosing and treating a cystic leakage with a BD stent. For each task, the total time required to complete the task, time required to correctly view the papilla, total time of irradiation, time to deep cannulation, time to define diagnosis, time to complete sphincterotomy, and time to complete the respective intervention were measured. Cannulation of the BD, correct diagnosis, sphincterotomy, and time to complete intervention were assessed by an assessor blinded to the status of the endoscopist who performed the virtual ERCP. Results The time required to visualize the papilla and to cannulate deeply when removing the BD stone was significantly shorter for the experts (both p < 0.05). The time to visualize the papilla, cannulate deeply, reach a diagnosis, complete sphincterotomy, and complete the intervention was significantly shorter for the experts when managing cystic leakage (all p < 0.05). In diagnosing and taking brush cytology from a hilar stenosis, there was only a trend toward the experts needing less time for the deep cannulation of the BD (p = 0.077). Conclusion The performance differed between experts and novices, especially in the management of cystic leakage. This corroborates the construct validity of the GI II Mentor simulator.